Off-hand grinding safety ([East Melbourne, Vic.] : Vocam Worldwide Publishing, 2003)
Demonstrates safe procedures in the use of off-hand grinding machines. Topics covered include handling and storage of wheels, selection and types of abrasive wheels, mounting of wheels, personal protective equipment, preparing the grinder and wheel for use and safe grinding procedures
Title from title screen
VCD format
Keywords: Grinding and polishing; Grinding wheels -- Safety measures; Grinding machines; Industrial safety -- Industrial accident prevention